PERENCANAAN BANGUNAN PENGENDALI SEDIMEN, ZONA NON CEKUNGAN AIR TANAH, HULU SUNGAI SERANG, WONOSEGORO, KABUPATEN BOYOLALI - Rizki Adi Prasetiyo; Adib Amali; Sri Eko Wahyuni; Robert J. Kodoatie (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2014)
The location plan of Wonosegoro Check Dam in the Upper Serang river, District of Wonosegoro regency of Boyolali, has the hydrogeological characteristics of Non ground water basin (Non CAT). The Serang Wonosegoro watershed has 177.16 km 2 area. The flood discharge plan obtained by the Rational method in the amount of 581.425 m3/second with a return period of 100 years. Check Dam has design by reinforced concrete with effective main dam height of 2 m, Sub Dam 1 m, and width 55 m, summit peak elevation of dam + 118.93 m above sea level and length of apron 26.390 m. Results of sediment transport by Ackers & White method is Qs = 5,174 tonnes / day. The magnitude of the rate of sedimentation in the Serang watershed amounted to 17.579 tons / ha / year. Time project of execution plan is 28 weeks with a budget plan is Rp. 6,422,807,000.00.